PENINGKATAN KEMAMPUAN APRESIASI CERPEN SISWA MELALUI TEKNIK ANALISIS UNSUR-UNSUR INTRINSIK - Nurmi, Nurmi (Universitas Negeri Makassar, 2018)
The purpose of this study is to increase students' appreciation of literary works. One technique that can be used is the analysis of intrinsic elements. Based on the results of data analysis during cycles I, II, and III it can be concluded that the results of the study are as follows: (1) the number of students who have a short reading interest increases (60% - 70%), (2) the number of students who have the ability to identify elements intrinsic increases (40% - 64%), (3) the number of students who have the ability to analyze intrinsic elements increases (40% - 60%). The results of the study also showed that there was a change in teachers becoming more concerned about the classroom atmosphere